DOI: 10.3384/diss.diva-133194
|View full text |Cite
|
Sign up to set email alerts
|

Speech masking speech in everyday communication: The role of inhibitory control and working memory capacity

Abstract: Speech masking speech in everyday communicationThe role of inhibitory control and working memory capacity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…Recent work has shown that next to working memory, inhibitory control also plays an important role in segregating target speech from distracting background noise. Older individuals with a hearing loss have been found to have more difficulties at switching their attention from irrelevant to relevant stimuli than normally hearing younger adults (Stenbäck ). Within this particular context, our study focuses on the potential negative effect of declining inhibitory control on speech‐in‐noise understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that next to working memory, inhibitory control also plays an important role in segregating target speech from distracting background noise. Older individuals with a hearing loss have been found to have more difficulties at switching their attention from irrelevant to relevant stimuli than normally hearing younger adults (Stenbäck ). Within this particular context, our study focuses on the potential negative effect of declining inhibitory control on speech‐in‐noise understanding.…”
Section: Introductionmentioning
confidence: 99%